Crosstalk between Gut Microbiota Metabolites and Ischemic Stroke - TANG Qiang (康复学报)
Gut microbiome is a key factor in health and disease transformation, and can metabolize nutrients consumed by human body to produce microbiota metabolites mainly composed of short-chain fatty acids (SCFAs), trimethylamine N-oxide (TMAO), tryptophan metabolites and secondary bile acids (2BAs), which are closely related to ischemic stroke (IS). Ischemic stroke is a refractory brain injury that results in severe loss of function and greatly increases the burden of society and medical system. Experiments have proved that regulating the microbiota metabolites can effectively improve the prognosis of stroke. Therefore, a full understanding of the crosstalk between ischemic stroke and microbiota metabolites will help to formulate the relevant treatment strategies, so as to guide clinical practice. This article summarized the formation and function of microbiota metabolites, the relationship with ischemic stroke, and the possible pathways of action, so as to provide new ideas for future research on ischemic stroke.